Mitigating MENA communitarian conflicts through power-sharing options - Salamey, Imad (2019)
The erosion of Arab nation states is attributed to an embedded legitimacy deficit and the deconstruction of geographic barriers. The latest proliferation of cross-national communal conflicts along sectarian, ethnic, and tribal lines expresses the clear intentions of communities to reconstruct the state and renegotiate new terms of the social contract. The politics of communitarian existentialism and collective mobilisations characterise contemporary contention, which calls for communitarian solutions to intercommunitarian problems. A communitocracy is proposed as a viable conflict-mitigating arrangement that assures communitarian powersharing based on the politics of consensus.